Monarchy and matrimony : the courtships of Elizabeth I - Doran, Susan (Routledge, 1996)
`An authoritative and accessible study of Elizabeth I's marriage negotiations.' Christopher Durston. Doran views the question of the Queen's celibacy within a wider political and religious context.